A kind of hemispherical cobalt coordination polymer and its composite material, preparation method and application
Patent Information
- Application Number
- CN202311145032.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-06
- Publication Date
- 2026-10-23
- Estimated Expiration
- 2043-09-06
AI Technical Summary
[0023]1、本发明的催化剂材料能够通过常见的水热法制备,制备方法简单易行,为催化硫醚的氧化反应提供了新的选择,同时利用绿色、环保、无毒的模拟太阳光氙灯提供光源,拓展了CP复合材料的应用价值;同时,反应结束后经简单离心过滤就可以回收催化剂,回收的催化剂可以继续催化该反应,并且循环10次以后,催化活性没有下降,显示出良好的催化活性,实验中表现出了很好的活性,表明具有很高的催化活性和环保性。
Smart Images

Figure CN117024764B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of inorganic materials technology, specifically relating to the preparation and application of a hemispherical cobalt coordination polymer (Co-CP-1) and its composite materials. Technical Background
[0002] Natural photosynthesis enables green plants, algae, and bacteria to capture photons, drive multi-electron chemical reaction processes, and convert solar energy into chemical substances (including carbohydrates, hydrogen, or oxygen). This is the foundation of life on Earth. To meet the growing demand for sustainable energy, researchers have begun to study artificial photocatalysis technologies that mimic natural photosynthesis, including the photocatalytic reduction of carbon dioxide to fuel and the photocatalytic splitting of water into hydrogen or oxygen, which have attracted widespread attention in recent years. The key to artificial photocatalysis technology is the artificial photocatalyst. Many semiconductors, including g-C3N4, MSx (M = Cd, Mo, and W), TiO2, BiOX (X = Cl, Br, or I), Nb2O5, conjugated polymers, and supported noble metal nanoparticles, have been selected as suitable photocatalysts.
[0003] Coordination polymers (CPs) are crystalline porous materials that have distinguished themselves among porous heterogeneous catalysts or catalyst supports due to their exceptionally large specific surface area, high porosity, tunable structure, and functionality. In recent years, photoactive CPs constructed from photoresponsive components have attracted widespread research interest and have been used as promising photocatalyst platforms. To date, some photoactive CPs, exhibiting excellent semiconductor properties, have been applied to photocatalytic reactions such as H₂O decomposition, CO₂ reduction, photodegradation of pollutants, and organic conversion reactions. More importantly, combining their high porosity and photoactivity, integrating CPs with inorganic semiconductors to construct heterojunction photocatalysts has been demonstrated by several groups, including ours, as an ideal strategy for robust photocatalysts. CP-based heterojunction photocatalysts help meet the requirements of highly efficient photocatalysts, such as suitable bandgap structures, improved light absorption, and charge separation efficiency. Summary of the Invention
[0004] To address the problems existing in the prior art, this invention provides a hemispherical cobalt coordination polymer and its composite material, preparation method, and application. This invention utilizes (3,5-dicarboxyphenyl chloroacetamide)(H2ctpa) as a multifunctional organic ligand, and obtains the cobalt coordination polymer (Co-CP-1)[Co(ctpa)2(4,4-bpe)2] through self-assembly with cobalt ions. n, n=∞; Subsequently, under the action of surfactant SDS, a micron-sized hemispherical cobalt coordination polymer hemispherical crystal material (Co-CP-2) is formed; then, through in-situ technology, CdS particles are grown in situ on the surface of Co-CP-2 to construct a CdS@Co-CP-2 material with good catalytic performance.
[0005] To solve the above-mentioned technical problems, the present invention adopts the following technical solution:
[0006] (1) Add Co(NO3)2·6H2O to 3ml of water and stir at room temperature to obtain reaction system a;
[0007] (2) Add H2ctpa and 4,4'-bpe to reaction system a in step (1) respectively, stir to obtain reaction system b, and place in an oven at 60-80℃ for 48-72h.
[0008] (3) The product after the reaction in step (2) was cooled to room temperature at a rate of 5℃ / h to obtain pink large-particle crystals. The crystals were washed with distilled water and acetonitrile in sequence and dried to obtain the cobalt coordination polymer Co-CP-1.
[0009] (4) Add SDS to reaction system b in step (2), seal the system, and place it in an oven at 60-80℃ for 48-72h to obtain red hemispherical crystals. Wash with distilled water and dry to obtain hemispherical micron cobalt coordination polymer material Co-CP-2.
[0010] The preparation method of the cadmium sulfide composite cobalt coordination polymer material CdS@Co-CP-2 of the present invention is as follows:
[0011] The hemispherical micron-sized cobalt coordination polymer material Co-CP-2 was added to an ethanol solution of Cd(CH3COO)2·2H2O, followed by the addition of an aqueous solution of thioacetamide. After sealing the system, it was placed in an oven at 40-80℃ for 1-3 hours, cooled to room temperature, centrifuged, and washed repeatedly with distilled water 3-5 times to obtain the target product, cadmium sulfide composite cobalt coordination polymer material CdS@Co-CP-2.
[0012] Furthermore, in step (2), H2ctpa is 3,5-dicarboxyphenyl chloroacetamide and 4,4'-bpe is 1,2-di(4-pyridyl)ethylene.
[0013] Furthermore, the molar ratio of Co(NO3)2·6H2O, H2ctpa, 4,4'-bpe and SDS is (0.04-0.06):(0.02-0.04):(0.03-0.05):(0.03-0.05).
[0014] Preferably, the molar ratio of Co(NO3)2·6H2O, H2ctpa, 4,4'-bpe and SDS is 0.04:0.02:0.04:0.03.
[0015] Furthermore, in step (4), the mass ratio of Co-CP-2, cadmium acetate, and thioacetamide is 0.05:(0.08-0.037):(0.002-0.011).
[0016] This invention also provides the application of cadmium sulfide-cobalt coordination polymer material CdS@Co-CP-2 in the photo-oxidation reaction of sulfides to synthesize sulfoxide derivatives. The CdS@Co-CP-2 catalytic material has high heterogeneous catalytic activity and high recovery rate. Under visible light irradiation, this material has good catalytic effect in the selective catalytic oxidation reaction of sulfides to synthesize sulfoxide derivatives.
[0017] The application of the CdS@Co-CP-2 catalytic material prepared by the above method in the photo-oxidation reaction of sulfides to synthesize sulfoxide derivatives includes the following steps:
[0018] (a) Place the thioether compound as a reaction substrate in a container.
[0019] (b) Based on 0.05 mmol substrate, 0.02 g of catalyst material was added, and then the mixture was irradiated with a xenon lamp at room temperature.
[0020] (c) By TLC monitoring, the catalytic conversion rate of sulfide compounds reached 100%, and the separation yield of the final product reached over 90%.
[0021] Using the composite material CdS@Co-CP as a heterogeneous catalyst, the photo-oxidation reaction of sulfide was catalyzed under visible light irradiation to synthesize sulfoxide derivatives. The results showed that the composite material CdS@Co-CP can catalyze the photo-oxidation reaction of sulfide with high selectivity under visible light irradiation, with a separation yield efficiency of over 90%.
[0022] The beneficial effects of this invention are:
[0023] 1. The catalyst material of this invention can be prepared by a common hydrothermal method, which is simple and easy to implement, providing a new option for catalyzing the oxidation reaction of sulfides. At the same time, it utilizes a green, environmentally friendly, and non-toxic simulated sunlight xenon lamp as a light source, expanding the application value of CP composite materials. Furthermore, the catalyst can be recovered by simple centrifugation and filtration after the reaction, and the recovered catalyst can continue to catalyze the reaction. After 10 cycles, the catalytic activity did not decrease, showing good catalytic activity. The experiment showed excellent activity, indicating that it has high catalytic activity and environmental friendliness.
[0024] 2. The catalyst material of this invention has good stability, and thermogravimetric analysis shows that it remains stable below 300℃. Figure 3 The experiment catalyzing the photo-oxidation reaction of sulfides to synthesize sulfoxides was conducted at room temperature; and SEM images after 10 catalytic cycles showed that the catalyst maintained its intact morphology during the catalytic process. Figure 17 This proves that the catalyst can be recycled and reused.
[0025] 3. The Co-CP-1 prepared in this application is a plate-like red crystal with a specific surface area of 4.57 m². 2 g -1 The catalytic materials composed of Cd-CP-2 and CdS@Co-CP hemispherical structures have specific surface areas of 12.39 m². 2 g -1 and 12.08m 2 g -1 Compared to Co-CP-1, Cd-CP-2 and CdS@Co-CP-2 have nearly three times the specific surface area, which facilitates the exposure of more easily accessible catalytic active centers to participate in catalytic reactions, thereby improving catalytic activity. Attached Figure Description
[0026] Figure 1 This is a structural diagram of the H2ctpa and 4,4'-bpe ligands used in material preparation.
[0027] Figure 2 This is a crystal unit structure diagram of the Co-CP-1 material prepared in Example 1.
[0028] Figure 3 This is a thermogravimetric analysis diagram of the Co-CP-1 material prepared in Example 1.
[0029] Figure 4 This is a comparison of powder XRD patterns of the Co-CP-1 material prepared in Example 1 and the Cd-CP-2 material prepared in Example 2.
[0030] Figure 5 This is a SEM image of Cd-CP-2 obtained in Example 2.
[0031] Figure 6 Yes, this is a side SEM image of Cd-CP-2 obtained in Example 2.
[0032] Figure 7 This is a SEM image of CdS@Co-CP-2a with a CdS mass fraction of 1%.
[0033] Figure 8 This is a SEM image of CdS@Co-CP-2b with a CdS mass fraction of 5%.
[0034] Figure 9 This is a SEM image of CdS@Co-CP-2c with a CdS mass fraction of 10%.
[0035] Figure 10 This is a SEM image of CdS@Co-CP-2d with a CdS mass fraction of 15%.
[0036] Figure 11 This is a SEM image of CdS@Co-CP-2e with a CdS mass fraction of 20%.
[0037] Figure 12 This is the NMR spectrum of the product synthesized from the photo-oxidation reaction of sulfoxide catalyzed by the CdS@Co-CP-2c composite material in Example 8.
[0038] Figure 13 This is the NMR spectrum of the product synthesized from the photo-oxidation reaction of sulfoxide catalyzed by the CdS@Co-CP-2c composite material in Example 9.
[0039] Figure 14 This is the NMR spectrum of the product synthesized from the photo-oxidation reaction of sulfoxide catalyzed by the CdS@Co-CP-2c composite material in Example 10.
[0040] Figure 15 This is the NMR spectrum of the product synthesized from the photo-oxidation reaction of sulfoxide catalyzed by the CdS@Co-CP-2c composite material in Example 11.
[0041] Figure 16 This is the NMR spectrum of the product synthesized from the photo-oxidation reaction of sulfoxide catalyzed by the CdS@Co-CP-2c composite material in Example 12.
[0042] Figure 17 This is a test diagram of the (CdS@Co-CP-2c) composite catalyst cycle experiment.
[0043] Figure 18 This is a SEM image of the CdS@Co-CP-2c catalyst composite material after a cycle experiment. Detailed Implementation
[0044] The following examples further illustrate the above-described content of the present invention, but it should not be construed as limiting the scope of the subject matter of the present invention to the following examples. All technologies implemented based on the above-described content of the present invention fall within the scope of the present invention.
[0045] Example 1
[0046] Preparation of red, plate-like crystalline Co-CP-1 material:
[0047] (1) Co(NO3)2·6H2O (0.0116 g, 0.04 mmol) was added to a 10 mL glass bottle, and 3 mL H2O was added. The mixture was stirred magnetically at room temperature to obtain reaction system a.
[0048] (2) Add H2ctpa (0.0048 g, 0.02 mmol) and 4,4'-bpe (0.0072 g, 0.04 mmol) to reaction system a and stir for 20 min to obtain reaction system b.
[0049] (3) After sealing the above reaction system b, place it in an 80℃ oven for 48 hours.
[0050] (4) After the reaction, red flaky crystals were obtained, washed with distilled water, and dried to obtain the target product Co-CP-1. Figure 1-3 Weigh the product. Yield: 70% (calculated based on Co(NO3)2·6H2O).
[0051] The crystallographic parameters of Co-CP-1 are detailed in the table below:
[0052]
[0053] Example 2 Preparation of hemispherical cobalt coordination polymer material Co-CP-2:
[0054] (1) Co(NO3)2·6H2O (0.0116 g, 0.04 mmol) was added to a 10 mL glass bottle, and 3 mL of H2O was added. The mixture was stirred magnetically at room temperature to obtain reaction system a.
[0055] (2) Add H2ctpa (0.0048 g, 0.02 mmol) and 4,4'-bpe (0.0072 g, 0.04 mmol) to the above reaction system a and stir for 10-20 min to obtain reaction system b.
[0056] (3) Add SDS (0.0086 g, 0.03 mmol) to the above reaction system b and stir for 10-20 min to obtain reaction system c.
[0057] (3) After sealing the above reaction system c, place it in an 80℃ oven for 48 hours.
[0058] (4) After the reaction was completed, red hemispherical crystals were obtained. These crystals were washed with distilled water and dried to obtain the target product Co-CP-2. Figure 4 , Figure 5 and Figure 6 ).
[0059] Figure 4This is a comparison of powder XRD patterns of the Co-CP-1 material prepared in Example 1 and the Cd-CP-2 material prepared in Example 2. From... Figure 4 It can be concluded that the XRD patterns of Co-CP-1 and Co-CP-2 materials are completely identical, further indicating that their internal structures are the same.
[0060] Example 3
[0061] Preparation of cadmium sulfide-cobalt coordination polymer (CdS@Co-CP-2a) catalytic material:
[0062] (1) Weigh 0.008 g of Cd(CH3COO)2·2H2O and add it to a 20 mL glass bottle, and add 8 mL of EtOH. Stir magnetically at room temperature for 10-30 min.
[0063] (2) Weigh 0.05 g of Co-CP-2 material from Example 2 and add it to the solution in (1).
[0064] (3) Dissolve 0.002 g of thioacetamide in 2 mL of H2O and add it dropwise into the glass bottle in (2).
[0065] (4) After sealing the above reaction system, place it in an 80°C oven for 1 hour.
[0066] (5) Cool to room temperature, centrifuge and wash repeatedly with H2O and EtOH 3-5 times to obtain CdS@Co-CP-2a composite catalyst.
[0067] Example 4
[0068] Preparation of cadmium sulfide-cobalt coordination polymer (CdS@Co-CP-2b) catalytic material:
[0069] (1) Weigh 0.011 g of Cd(CH3COO)2·2H2O and add it to a 20 mL glass bottle, and add 8 mL of EtOH. Stir magnetically at room temperature for 10-30 min.
[0070] (2) Weigh 0.05 g of Co-CP-2 material from Example 2 and add it to the solution in (1).
[0071] (3) Dissolve 0.003 g of thioacetamide in 2 mL of H2O and add it dropwise into the glass bottle in (2).
[0072] (4) After sealing the above reaction system, place it in a 60°C oven for 2 hours.
[0073] (5) Cool to room temperature, centrifuge and wash repeatedly with H2O and EtOH 3-5 times to obtain the CdS@Co-CP-2b composite catalyst.
[0074] Example 5
[0075] Preparation of cadmium sulfide-cobalt coordination polymer (CdS@Co-CP-2c) catalytic material:
[0076] (1) Weigh 0.015 g of Cd(CH3COO)2·2H2O and add it to a 20 mL glass bottle, and add 8 mL of EtOH. Stir magnetically at room temperature for 10-30 min.
[0077] (2) Weigh 0.05 g of Co-CP-2 material from Example 2 and add it to the solution in (1).
[0078] (3) Dissolve 0.005 g of thioacetamide in 2 mL of H2O and add it dropwise into the glass bottle in (2).
[0079] (4) After sealing the above reaction system, place it in a 40°C oven for 3 hours.
[0080] (5) Cool to room temperature, centrifuge and wash repeatedly with H2O and EtOH 3-5 times to obtain the CdS@Co-CP-2c composite catalyst.
[0081] Example 6
[0082] Preparation of cadmium sulfide-cobalt coordination polymer (CdS@Co-CP-2d) catalytic material:
[0083] (1) Weigh 0.023 g of Cd(CH3COO)2·2H2O and add it to a 20 mL glass bottle, and add 8 mL of EtOH. Stir magnetically at room temperature for 10-30 min.
[0084] (2) Weigh 0.05 g of Co-CP-2 material from Example 2 and add it to the solution in (1).
[0085] (3) Dissolve 0.007 g of thioacetamide in 2 mL of H2O and add it dropwise into the glass bottle in (2).
[0086] (4) After sealing the above reaction system, place it in an 80°C oven for 1 hour.
[0087] (5) Cool to room temperature, centrifuge and wash repeatedly with H2O and EtOH 3-5 times to obtain the CdS@Co-CP-2d composite catalyst.
[0088] Example 7
[0089] Preparation of cadmium sulfide-cobalt coordination polymer (CdS@Co-CP-2e) catalytic material:
[0090] (1) Weigh 0.037 g of Cd(CH3COO)2·2H2O and add it to a 20 mL glass bottle, and add 8 mL of EtOH. Stir magnetically at room temperature for 10-30 min.
[0091] (2) Weigh 0.05 g of Co-CP-2 material from Example 2 and add it to the solution in (1).
[0092] (3) Dissolve 0.011 g of thioacetamide in 2 mL of H2O and add it dropwise into the glass bottle in (2).
[0093] (4) After sealing the above reaction system, place it in a 60°C oven for 2 hours.
[0094] (5) Cool to room temperature, centrifuge and wash repeatedly with H2O and EtOH 3-5 times to obtain CdS@Co-CP-2e composite catalyst.
[0095] Example 8
[0096] Example 4 describes the catalytic oxidation of methyl phenyl sulfide using the prepared catalyst CdS@Co-CP-2c, following the steps outlined below:
[0097] (1) Weigh 0.062 g of methyl phenyl sulfide (0.5 mmol) into a round-bottom flask and add acetonitrile (5 mL) as solvent.
[0098] (2) Add the composite material Co-CP-3c (0.02 g) to the reaction system of (1) as a catalyst.
[0099] (3) Then place the reaction system (2) under a xenon lamp for illumination and react at room temperature.
[0100] (4) After the reaction was complete, dichloromethane (DCM) was added to quench the reaction, followed by centrifugation, filtration, and rotary evaporation. The separation yield was 94%. 1 ¹H NMR (400MHz, CDCl₃): δ 7.65 (d, J = 8.0Hz, 2H), 7.56–7.47 (m, 3H), 2.72 (s, 3H); For example Figure 12 As shown.
[0101] Example 9
[0102] Example 4 describes the catalytic oxidation of 4-chlorophenyl methyl sulfide using the catalyst CdS@Co-CP-2c prepared in the following steps:
[0103] (1) Weigh 0.079 g of 4-chlorophenylmethyl sulfide (0.05 mmol) into a round-bottom flask and add acetonitrile (5 mL) as solvent.
[0104] (2) Add the composite material Co-CP-3c (0.02 g) to the reaction system of (1) as a catalyst.
[0105] (3) Then place the reaction system (2) under a xenon lamp for illumination and allow it to react at room temperature.
[0106] (4) After the reaction was complete, dichloromethane (DCM) was added to quench the reaction, followed by centrifugation, filtration, and rotary evaporation. The separation yield was 92%. 1 H NMR (400MHz, CDCl3): δ7.59 (d, J = 8.0 Hz, 2H), 7.51 (d, J = 8.0 Hz, 2H), 2.72 (s, 3H); such as Figure 13 As shown.
[0107] Example 10
[0108] Example 4 describes the catalytic oxidation of 4-methoxyanisole using the CdS@Co-CP-2c catalyst, with the following steps:
[0109] (1) Weigh 0.077 g of 4-methoxyanisole (0.05 mmol) into a round-bottom flask and add acetonitrile (5 mL) as solvent.
[0110] (2) Add the composite material Co-CP-3c (0.02 g) to the reaction system of (1) as a catalyst.
[0111] (3) Then place the reaction system (2) under a xenon lamp for illumination and allow it to react at room temperature.
[0112] (4) After the reaction was complete, dichloromethane (DCM) was added to quench the reaction, followed by centrifugation, filtration, and rotary evaporation. The separation yield was 92%. 1 ¹H NMR (400MHz, CDCl₃): δ 7.57–7.62 (m, 2H), 7.01–7.06 (m, 2H), 3.86 (s, 3H), 2.70 (s, 3H). (e.g.) Figure 14 As shown.
[0113] Example 11
[0114] Example 4 describes the catalytic oxidation of n-butyl sulfide using the catalyst CdS@Co-CP-2c prepared in the following steps:
[0115] (1) Weigh n-Butyl sulfide (0.073 g, 0.05 mmol) into a round-bottom flask and add acetonitrile (5 mL) as solvent.
[0116] (2) Add the composite material CdS@Co-CP-3c (0.02 g) to the reaction system of (1) as a catalyst.
[0117] (3) Then place the reaction system (2) under a xenon lamp for illumination and allow it to react at room temperature.
[0118] (4) After the reaction is complete, dichloromethane (DCM) is added to quench the reaction, followed by centrifugation, filtration, and rotary evaporation. The separation yield is 90%. Figure 15 As shown.
[0119] Example 12
[0120] Example 4 describes the catalytic oxidation of 3-bromothioanisole using the catalyst CdS@Co-CP-2c prepared in the following steps:
[0121] (1) Weigh 0.010 g of 3-bromothioanisole (0.05 mmol) into a round-bottom flask and add acetonitrile (5 mL) as solvent.
[0122] (2) Add the composite material Co-CP-3c (0.02 g) to the reaction system of (1) as a catalyst.
[0123] (3) Then place the reaction system (2) under a xenon lamp for illumination and allow it to react at room temperature.
[0124] (4) After the reaction is complete, dichloromethane (DCM) is added to quench the reaction, followed by centrifugation, filtration, and rotary evaporation. The separation yield is 94%. Figure 16 As shown.
[0125] Example 13
[0126] The following steps describe the catalytic oxidation reaction of methyl phenyl sulfide compounds using recycled catalyst CdS@Co-CP-2c to synthesize methyl phenyl sulfide:
[0127] (1) The composite material CdS@Co-CP-2c separated by filtration in Example 8 was added again as a catalyst to a mixture containing methyl phenyl sulfide (0.062 g, 0.05 mmol) and acetonitrile (5 mL).
[0128] (2) Then place the reaction system (1) under a xenon lamp for illumination and react at room temperature.
[0129] (3) After the reaction is complete, dichloromethane (DCM) is added to quench the reaction, centrifuge, filter, and the catalyst material CdS@Co-CP-2c is obtained again.
[0130] (4) The composite material CdS@Co-CP-2c separated by filtration was used as a catalyst to continue the experiment in the same amount as in Example 8.
[0131] (5) The catalyst is recycled ten times using the method described above, with the specific method being the same as above. Figure 17-18 ).
[0132] The above embodiments describe the basic principles, main features, and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited to the above embodiments. The embodiments and descriptions in the specification are only illustrative of the principles of the present invention. Various changes and modifications can be made to the present invention without departing from the scope of the principles of the present invention, and all such changes and modifications fall within the protection scope of the present invention.
Claims
1. A method for preparing a hemispherical cobalt coordination polymer, characterized in that... Includes the following steps: (1) Add Co(NO3)2·6H2O to deionized water and stir at room temperature to obtain reaction system a; (2) Add H2ctpa and 4,4'-bpe to reaction system a in step (1) respectively, and stir to obtain reaction system b; (3) Sodium dodecyl sulfate (SDS) was added to reaction system b in step (2). After the system was sealed, it was placed in an oven at 60-80℃ for 48-72h to obtain red hemispherical crystals. The crystals were washed with distilled water and dried to obtain hemispherical cobalt coordination polymer Co-CP-2. In step (2), H2ctpa is 5-(2-chloroacetamido)benzene-1,3-dicarboxylic acid, and 4,4'-bpe is 1,2-bis(4-pyridyl)ethylene; The molar ratio of Co(NO3)2·6H2O, H2ctpa, 4,4'-bpe and SDS is (0.04-0.06):(0.02-0.04):(0.03-0.05):(0.03-0.05).
2. The method for preparing the hemispherical cobalt coordination polymer according to claim 1, characterized in that: The molar ratio of Co(NO3)2·6H2O, H2ctpa, 4,4'-bpe and SDS is 0.04:0.02:0.04:0.
03.
3. The hemispherical cobalt coordination polymer Co-CP-2 prepared by the preparation method according to claim 1 or 2.
4. A method for preparing a cadmium sulfide composite cobalt coordination polymer material, characterized in that: The hemispherical cobalt coordination polymer Co-CP-2 described in claim 3 was added to an ethanol solution of Cd(CH3COO)2·2H2O, followed by the addition of an aqueous solution of thioacetamide. After sealing the system, it was placed in an oven at 40-80℃ for 1-3 hours, cooled to room temperature, centrifuged, and washed repeatedly with distilled water 3-5 times to obtain the target product, cadmium sulfide composite cobalt coordination polymer material CdS@Co-CP-2.
5. The method for preparing the cadmium sulfide composite cobalt coordination polymer material according to claim 4, characterized in that: The mass ratio of the hemispherical cobalt coordination polymer Co-CP-2, Cd(CH3COO)2·2H2O and thioacetamide is 0.05:(0.08-0.037):(0.002-0.011).
6. The application of the cadmium sulfide cobalt coordination polymer CdS@Co-CP-2 prepared by the preparation method according to claim 4 or 5 as a catalyst material in the selective photocatalytic oxidation synthesis of sulfoxide derivatives.
7. The application according to claim 6, characterized in that: The thioether compound was placed in a container as a reaction substrate, and CdS@Co-CP-2 catalyst was added. The reaction was carried out at room temperature under visible light irradiation and stirred for 1-3 hours to complete the catalytic reaction.